Monitoring of forest fires at the local scale: case study of the ejido Mecayapan, Mexico - Neger, Christoph; García López, Paula; Manzo Delgado, Lilia de Lourdes; Espinoza Rodríguez, José Manuel (BOSQUE, 2023)
Studies focused on the monitoring of forest fires generally are based on field registers and data from satellite analysis, and very few consider both sources. However, both have limitations, like the inaccuracy of field data as well as clouds, which hamper remote sensing. The present paper revises the available sources for the identification of burnt areas of tropical rainforest, pine and oak forest in the ejido Mecayapan, Mexico, in the years 2016 to 2020. Burnt areas identified on satellite images, thermal hotspots and field data from the institutions involved in fire management were compared, using a geographic information system. The study shows that the combination of diverse sources is of great utility, allowing it to obtain a more complete vision of the total burnt surface and the ecosystems affected by wildfires. Based on this result, it is recommended to establish collaboration networks for fire monitoring, which include both actors involved in fire management and entities specialized in satellite analysis.